The relationship between responsible leadership and individual creativity: The role of affective commitment - Simões, L. M.; Duarte, A. P.; Ribeiro, N. (Proceedings of the International Conference of Applied Business and Management (ICABM2022), 2022)
Purpose: Leadership is one of the main topics in organizational behavior. Over the years, many researchers have studied the impact of different leadership styles on the attitudes and behaviors of employees. However, perhaps because it is a relatively recent construct, little research has been devoted to analyzing the effect that responsible leadership has at the individual level of analysis (Haque et al., 2019, 2020; Miska & Mendenhall, 2018). Starting from the identification of this gap, the present research adopted an employee-centered approach to analyze how responsible leadership is related to individual creativity within the scope of a model that proposes affective commitment as a potential mediating mechanism. Recent research has found empirical support for the existence of a direct positive relationship between the variables (Castro-González et al., 2019). Research has also established a positive relationship between responsible leadership and affective commitment (Haque et al. 2019, 2020; Mousa, 2017; Simões & Duarte, 2021). Several studies on positive leadership styles have established affective commitment as a relevant mediating variable between leadership and employees’ attitudinal, emotional, and behavioral responses (Asif et al., 2019; Duarte et al., 2021). It is possible to theorize that responsible leadership, being also a positive leadership style, will find similar results, contributing to a greater employee emotional attachment to the organization, which will lead to more individual creativity behaviors at work.